Determinación del potencial agroclimático para la producción de caña de azúcar (Saccharum officinarum L.) en Costa Rica - Rojas, O.E; Eldin, M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The agroclimatic potential of sugar cane is defined by estimating a production function for dry matter, performing a rainfall frequential analysis, and calculating a climatic ripening index. This requires the use of data on temperature (daily and diurnal), precipitation (daily) and solar radiation (daily). Climatic data from five weather stations representing the major physical-geographic regions of Costa Rica was used in this study. In addition, the growing seasons and optimal harvest tunes were determined.